UJI SINERGITAS ANTIFUNGAL FLUCONAZOLE DENGAN MINYAK ATSIRI CYMBOPOGON CITRATUS TERHADAP JAMUR CANDIDA ALBICANS - Sharon Claudia Ethelyn Sihole; Sandy Vitria Kurniawan (Atma Jaya Catholic University of Indonesia, 2021)
Introduction: Candida albicans is a common human flora. However, if the amount is above average, it can cause a disease called candidiasis. Fluconazole is an antifungal medication that can cure candidiasis but its number of resistance is increasing. Therefore alternative treatments are needed like using herbs. Cymbopogon citratus essential oil is proven to have an antifungal effect. The purpose of this study is to see the synergistic antifungal effect of fluconazole combined with lemongrass against C. albicans. Methods: Experimental study design was used in this research and conducted in vitro. C. citratus was extracted with hydrodistillation method. Disc diffusion method was performed using MHA agar with Glucose 2% and methylene blue. Lemongrass essential oil concentration that are used are 2,5%, 5%, 10%, and 20% using tween as a solvent. Results: Minimum concentration of lemongrass essential oil that could inhibit C. albicans growth is 10% with average diameter of inhibition zone 10 mm. Minimum concentration of fluconazole combined with lemongrass essential oil that could inhibit C. albicans growth is 2,5% with average diameter 21,3333 mm. Average diameter of inhibition zone by fluconazole combined with lemongrass essential oil is greater than fluconazole’s inhibition zone added with lemongrass essential oil inhibition zone alone, therefore fluconazole combined with C. citratus essential oil work synergistically. Conclusion: There is a synergistic antifungal effect of fluconazole combined with C. citratus essential oil against C. albicans. Key Words: Candida albicans, Cymbopogon citratus, fluconazole, synergistic